The Lunar Radiation Environment: Comparisons between PHITS, HETC-HEDS, and the CRaTER Instrument - Fahad A. Zaman (Aerospace, 2021)
Understanding the radiation environment near the lunar surface is a key step towards planning for future missions to the Moon. However, the complex variety of energies and particle types constituting the space radiation environment makes the process of replicating such environment very difficult in Earth-based laboratories. Radiation transport codes provide a practical alternative covering a wider range of particle energy, angle, and type than can be experimentally attainable. Comparing actual measurements with simulation results help in validating particle flux input models, and input collision models and databases involving nuclear and electromagnetic interactions. Thus, in this work, we compare the LET spectra simulated using the Monte Carlo transport code PHITS with measurements made by the CRaTER instrument that is currently orbiting the Moon studying its radiation environment. In addition, we utilize a feature in PHITS that allows the user to run the simulations without Vavilov energy straggling to test whether it is the root cause of erroneous phenomena exhibited in similar studies in literature. The results herein show good agreement between the LET spectra of PHITS and the CRaTER instrument. They also confirm that using a Vavilov distribution correction would ultimately provide a better agreement between CRaTER measurements and the previous LET spectra from the transport codes HETC-HEDS and HZETRN.